High-sodium-content P2-phase manganese-based composite positive electrode material, preparation method and battery

The preparation of manganese-based composite cathode material with high sodium content P2 phase through the sol-gel method solves the problems of high price and unstable structure of Ni elements, and achieves high specific capacity, excellent circulation performance and good safety performance of the material, which is suitable for commercial production.

CN119864413AActive Publication Date: 2025-04-22INNER MONGOLIA UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510336154.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-22
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The Ni element in the existing high sodium content P2 phase positive electrode materials is expensive and toxic, affecting the cost and safety of materials. At the same time, the orderly arrangement of Na+/vacancies leads to structural instability, affecting the circulation performance of sodium ion batteries.

Method used

The sol-gel method is used to prepare manganese-based composite cathode material with high sodium content P2 phase. By adjusting the doping elements and proportions, the Ni content is reduced, and the costly Fe elements are introduced to improve the safety and circulation stability of the material.

Benefits of technology

It achieves high specific capacity, excellent circulation performance and good safety performance of the material, reduces production costs, is suitable for commercial production, and is suitable for solar energy, wind power generation, electric vehicles and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864413A_ABST
    Figure CN119864413A_ABST
Patent Text Reader

Abstract

The invention relates to a high-sodium-content P2-phase manganese-based composite positive electrode material, a preparation method and a battery, the chemical general formula of the manganese-based composite positive electrode material is NaxMy1Ny2Fey3MnzO2, x, y1, y2, y3 and z are molar percentages of corresponding elements respectively, and the relations among y1, y2, y3 and z meet the following conditions: y1 + y2 + y3 + z = 1, 0.75 < = x < = 0.9, 0 < y1 < = 0.2, 0 < y2 < = 0.2, 0.05 < = y3 < = 0.2, and 0.6 < = z < = 0.9; m comprises at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; n comprises at least one of Ni, Mg and Cu; the working voltage of the sodium ion battery prepared from the manganese-based composite positive electrode material is 2-4.3 V, and the sodium ion battery has the characteristics of good electrochemical performance, high safety performance and wide application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a manganese-based composite positive electrode material of a P2 phase with a high sodium content, a preparation method and a battery. Background Art

[0002] Sodium-ion batteries have attracted widespread attention due to their abundant sodium resources and low cost. The preparation of cathode materials with excellent performance is the key to the practical application of sodium-ion batteries. Among the many cathode materials, layered oxides have a higher specific capacity than other types of materials when used as battery cathode materials, so they have become a hot topic of extensive research. Layered oxides mainly have two structures: P2 phase layered oxides and O3 phase layered oxides. Among them, P2-type layered transition metal oxides (Na x TMO 2 , where TM represents transition metal) positive electrode has attracted widespread attention from researchers due to its advantages such as large specific capacity, high ionic conductivity and easy synthesis.

[0003] In the P2-type structure, the unique site occupation of sodium ions and the strong Na-Na and Na-TM electrostatic interactions usually lead to a distinct Na + / Vacancies are arranged in an orderly manner. Different Na + / vacancies orderly rearrangement produces a metastable phase, resulting in many voltage platforms in the charge and discharge curve of the P2 type cathode material, thus affecting the Na + Diffusion between layers and the cycling performance of the material. + Shielding the transition metal layer (TMO 2 ) between the electrostatic repulsion, during the charging process Na + The sodium layer weakens the shielding of TMO 2 The layer slides, resulting in lattice distortion, which limits its future commercial application. Especially for manganese-based materials, since the phase change of manganese-based positive electrode materials is more complicated and the average voltage of manganese-based materials is lower (<2.8V), although its specific capacity is relatively higher, its practical application is still greatly limited.

[0004] Therefore, if more Na can be retained in the P2 structure during the charge and discharge process, the Na + / vacancies are arranged in an orderly manner, which relieves the electrostatic repulsion between TM layers and better maintains the stability of the structure. Most of the high sodium content P2 phase positive electrode materials proposed so far are based on P2-Na 0.67 Ni 0.33 Mn 0.67 O 2Based on P2, the material has a low Mn content and a high Ni content. However, the high price of Ni element will have a great impact on the cost of the material and is not conducive to industrial production, but as the Ni content decreases, the inherent properties of the material may decay; in addition, a high content of Ni has a certain toxicity, which is not conducive to safe production. So, how to retain more sodium in the P2 structural body, thereby maintaining or improving the performance of P2-type layered transition metal oxide materials, while reducing the Ni content in the material is what we want to study. Summary of the invention

[0005] The purpose of the present invention is to address the problems existing in the prior art and to propose a manganese-based composite positive electrode material with a high sodium content P2 phase, a preparation method and a battery.

[0006] The method for preparing a high sodium content P2 phase manganese-based composite positive electrode material provided in an embodiment of the present invention obtains a series of high sodium content P2 phase manganese-based composite positive electrode materials for sodium ion batteries with excellent cycle life and rate capability and high specific capacity. The material contains extremely low amounts of Ni or no Ni, which reduces the cost of the material and improves safety. At the same time, by adjusting the doped elements and proportions, the large polarization and low capacity retention rate that may be caused by the Fe element are eliminated. Since the raw materials are cheap and readily available, they are suitable for commercial production and have extremely excellent practical application prospects, and can be widely used in the fields of solar energy, wind power generation, electric vehicles, etc.

[0007] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a manganese-based composite positive electrode material with a high sodium content P2 phase, wherein the chemical formula of the manganese-based composite positive electrode material is: Na x M y1 N y2 Fe y3 Mn z O 2 , wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9; M is an element doped to replace Mn in the transition metal position, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; N is an element doped to replace Mn in the transition metal position, including at least one of Ni, Mg and Cu.

[0008] The operating voltage of the manganese-based composite positive electrode material when used in a sodium ion battery is between 2V and 4.3V.

[0009] Preferably, the manganese-based composite positive electrode material is used in a sodium ion battery. During the first week of charging, the iron ions are oxidized from positive trivalent to positive tetravalent, while the manganese ions are oxidized from positive trivalent to positive tetravalent, and the oxygen ions are oxidized from negative divalent (O 2- ) is oxidized to negative one (O - ); During the first cycle of discharge, the iron ions are reduced from positive tetravalent to positive trivalent, while the manganese ions are reduced from positive tetravalent to positive trivalent, and the oxygen ions are reduced from negative monovalent (O - ) is reduced to negative divalent (O 2- ).

[0010] When the manganese-based composite positive electrode material contains nickel elements, during the first week of charging, the nickel ions will first be oxidized from positive divalent to positive trivalent, and then from positive trivalent to positive tetravalent; during the first week of discharging, the nickel ions will first be reduced from positive tetravalent to positive trivalent, and then from positive trivalent to positive divalent.

[0011] Other elements in the manganese-based composite positive electrode material do not undergo valence changes.

[0012] The valence change process of the manganese-based composite positive electrode material after the first cycle of charge and discharge is consistent with the valence change process of the first cycle of charge and discharge.

[0013] Preferably, the space group of the manganese-based composite positive electrode material is P6 3 / mmc, P6 3 22 or P6 3 / mcm, the crystal structure is P2 phase.

[0014] In a second aspect, an embodiment of the present invention provides a method for preparing the manganese-based composite positive electrode material with a high sodium content P2 phase as described in the first aspect above, and the preparation method is a sol-gel method, including.

[0015] According to the stoichiometric ratio of the chemical formula of the manganese-based composite positive electrode material, a sodium source material, a manganese source material, an iron source material, a compound containing the M element and a compound containing the N element are weighed as raw materials, the raw materials are dissolved in deionized water, a chelating agent is added after stirring and mixing, and stirring is continued at a certain temperature to form a precursor gel.

[0016] The precursor gel is placed in a muffle furnace and carbonized in an air atmosphere to obtain an intermediate product powder.

[0017] The intermediate product powder is pressed into discs, calcined in an air atmosphere, and then naturally cooled to room temperature to obtain the manganese-based composite positive electrode material with a high sodium content P2 phase.

[0018] The chemical formula of the manganese-based composite positive electrode material is: Na x M y1 N y2 Fe y3 Mnz O 2 , wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9; M is an element doped to replace Mn in the transition metal position, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; N is an element doped to replace Mn in the transition metal position, including at least one of Ni, Mg and Cu.

[0019] Preferably, the sodium source material includes: one or more of sodium nitrate, sodium acetate, sodium carbonate, sodium bicarbonate, sodium oxalate, and sodium hydroxide.

[0020] The manganese source material includes: manganese nitrate and / or manganese acetate.

[0021] The iron source material includes at least one of ferric nitrate, ferrous acetate, ferrous oxalate and ferrous lactate.

[0022] The compounds containing M elements include: 2+ , Li + , Nb 5+ , Ca 2+ , B 3+ 、Al 3+ 、Zr 4+ Sn 4+ 、Ti 4+ 、Ru 4+ , Sb 5+ Or Mo 6+ A compound containing at least one ion.

[0023] The compounds containing N element include: 2+ Mg 2+ , Cu 2+ A compound containing at least one ion.

[0024] The complexing agent is citric acid monohydrate; the mass ratio of the complexing agent to the raw material is 2:1.

[0025] The mass ratio of the deionized water to the raw material is 20:1 to 30:1.

[0026] Preferably, the carbonization treatment comprises: heating to 300° C. to 500° C. at a heating rate of 2° C. / min to 8° C. / min, and keeping the temperature for 1 hour to 4 hours in an air atmosphere.

[0027] Preferably, the calcination treatment comprises: heating to 800° C. to 1000° C. at a heating rate of 2° C. / min to 8° C. / min, and calcining for 10 to 20 hours in an air atmosphere.

[0028] In a third aspect, an embodiment of the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the manganese-based composite positive electrode material of the high sodium content P2 phase described in the first aspect above.

[0029] In a fourth aspect, an embodiment of the present invention provides a sodium ion battery, which includes the positive electrode plate described in the third aspect above; the sodium ion battery also includes a diaphragm, an electrolyte or a solid electrolyte, and a negative electrode plate.

[0030] The operating voltage range of the sodium ion battery is between 2V and 4.3V.

[0031] In a fifth aspect, an embodiment of the present invention provides a use of the sodium ion battery described in the fourth aspect above, wherein the sodium ion battery is used in one or more of solar energy, wind power generation, smart grid peak regulation, distributed power stations, backup power supplies, communication base stations, and energy storage devices for electric vehicles.

[0032] An embodiment of the present invention provides a method for preparing a manganese-based composite positive electrode material with a high sodium content P2 phase, wherein the raw materials are subjected to a sol-gel method to form a precursor gel, and then subjected to a carbonization and calcination process to obtain a manganese-based composite positive electrode material with a high sodium content P2 phase; the preparation method is simple to operate, the raw materials are cheap and easily available, the cost is low, and it can be suitable for large-scale production.

[0033] The high sodium content P2 phase manganese-based composite positive electrode material obtained by the preparation method provided in the embodiment of the present invention, firstly, the higher sodium content can effectively improve the first-week coulomb efficiency, first-week charging capacity and cycle stability of the material and can inhibit the material from the P2 phase to the O2 phase transformation under the high voltage range; secondly, the low-cost Fe element is introduced into the material to replace the Ni element, and the Fe element and the Mn element work synergistically to reduce the content of the Ni element to an extremely low level or completely exclude the Ni element, which not only reduces the material cost, but also improves the safety of the material, which is conducive to industrial production. At the same time, by adjusting the proportion of each element in the material, the problems of large polarization and poor cycle stability that may be caused by the Fe element are avoided.

[0034] The sodium ion battery prepared by using the manganese-based composite positive electrode material with a high sodium content P2 phase provided by the embodiment of the present invention has the characteristics of high specific capacity, excellent cycle performance, good safety performance and high practical value; the sodium ion battery containing the manganese-based composite positive electrode material with a high sodium content P2 phase is widely used and can be applied to large-scale energy storage equipment such as solar power generation, wind power generation, electric vehicles, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A flow chart of a method for preparing a manganese-based composite positive electrode material with a high sodium content P2 phase provided in an embodiment of the present invention.

[0036] Figure 2 A flow chart of a method for preparing a positive electrode sheet using a manganese-based composite positive electrode material with a high sodium content P2 phase as a positive electrode active material provided in an embodiment of the present invention.

[0037] Figure 3 X-ray diffraction (XRD) diagram of the manganese-based composite positive electrode material with a high sodium content P2 phase prepared in Examples 1-10 of the present invention.

[0038] Figure 4 This is the XRD diagram of the manganese-based composite positive electrode material with a high sodium content P2 phase prepared in Examples 11-14 of the present invention.

[0039] Figure 5 The first week charge and discharge curves of the batteries assembled in Example 1, Example 2 and Example 5.

[0040] Figure 6 The manganese-based composite positive electrode material Na prepared in Example 2 is a high sodium content P2 phase 0.8 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 Charge and discharge curves of the assembled battery from the first to the fifth week.

[0041] Figure 7 100-cycle capacity curves of the batteries assembled from Example 1, Example 2, and Example 5.

[0042] Figure 8 The manganese-based composite positive electrode material Na prepared in Example 5 is a P2 phase with a high sodium content. 0.8 Li 0.07 Ni 0.11 Fe 0.12 Mn 0.7 O 2 Charge and discharge curves of the assembled battery from the first to the fifth week.

[0043] Fig. 9 100-cycle capacity curves of the batteries assembled from Example 3, Example 4, and Examples 6-10.

[0044] Fig.10 This is a rate performance test diagram of the battery assembled in Example 5.

[0045] Fig.11The first week charge and discharge curves of the batteries assembled in Examples 11-14.

[0046] Fig.12 The manganese-based composite positive electrode material Na prepared in Example 11 is a high sodium content P2 phase 0.8 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 Charge and discharge curves of the assembled battery from the first to the fifth week.

[0047] Fig.13 100-cycle capacity curves of the batteries assembled in Examples 11-14.

[0048] Fig.14 Na prepared in Comparative Example 1 0.67 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 The charge and discharge curves of the battery assembled with the materials from the first to the fifth week.

[0049] Fig.15 This is a comparison chart of the first week charge and discharge curves of the batteries assembled in Example 2 and Comparative Example 1.

[0050] Fig.16 It is a comparison chart of the 100-cycle capacity curves of the batteries assembled in Example 2 and Comparative Example 1.

[0051] Fig.17 Na prepared in Comparative Example 2 0.67 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 The charge and discharge curves of the battery assembled with the materials from the first to the fifth week.

[0052] Fig.18 The first week charge and discharge curves of the batteries assembled in Example 11 and Comparative Example 2 are shown.

[0053] Fig.19 100-week cycle capacity curve of the batteries assembled in Example 11 and Comparative Example 2. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0056] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0057] The embodiment of the present invention provides a manganese-based composite positive electrode material with a high sodium content P2 phase, the general chemical formula of which is: Na x M y1 N y2 Fe y3 Mn z O 2 , where x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9. The value of x may be any value within the range of 0.6 to 0.9, such as 0.6, 0.7, 0.8, 0.9, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0058] In the manganese-based composite positive electrode material of the present invention, a higher sodium content can effectively improve the first-cycle coulomb efficiency, first-cycle charging capacity and cycle stability of the material, and can inhibit the material from changing from the P2 phase to the O2 phase under a high voltage range, thereby avoiding the problem of a decrease in initial coulomb efficiency and overall capacity, poor cycle stability and deterioration of rate performance due to phase change of the material, and obvious voltage hysteresis during charging and discharging. The reason is that in conventional manganese-based P2-type layered oxide positive electrode materials for sodium ion batteries, the unique occupation mode of sodium ions and the strong Na-Na and Na-TM electrostatic interactions usually cause the sodium layer to show obvious Na + / vacancies are arranged in an orderly manner. At the same time, Na + Shielding the transition metal layer (TMO 2 ) between the electrostatic repulsion, during the charging process Na + The sodium layer weakens the shielding of TMO 2The layer slides, resulting in lattice distortion. This lattice distortion means that during the charge and discharge process, especially in the high voltage range, the material structure changes, which may not only transform from P2 phase to O2 phase, but also transform to other structures such as OP4 phase. Therefore, during the charge and discharge process, if more Na can be retained in the P2 structure body, the shielding of the sodium layer during the charging process can be enhanced, making TMO 2 The sliding of the layers is weakened, inhibiting the Na + / vacancies are arranged in an orderly manner, which can better maintain the stability of the structure. Therefore, when the sodium content in the high sodium content P2 phase manganese-based composite positive electrode material provided by the embodiment of the present invention is high, not only can more Na + After the Na is released, more Na can remain in the structure to play a supporting role and inhibit structural distortion.

[0059] The value of y1 can be any value in the range of 0 to 0.2, for example, 0, 0.05, 0.1, 0.15, 0.2, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0060] The value of y2 can be any value in the range of 0 to 0.2, for example, 0, 0.05, 0.1, 0.15, 0.2, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0061] The value of y3 can be any value in the range of 0.05 to 0.2, for example, 0, 0.05, 0.1, 0.15, 0.2, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0062] The value of z can be any value in the range of 0.6 to 0.9, for example, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, etc., but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0063] M is an element that is doped to replace the transition metal site Mn, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo.

[0064] N is an element for doping and replacing the transition metal site Mn, including at least one of Ni, Mg, and Cu.

[0065] The crystal structure of the manganese-based composite cathode material is P2 and the phase space group is P6 3 / mmc, P6 3 22 or P6 3 Any space group in / mcm.

[0066] When the manganese-based composite positive electrode material is used in sodium-ion batteries, the operating voltage of the sodium-ion batteries is between 2V and 4.3V.

[0067] During the first cycle of charge and discharge of sodium-ion batteries, charge compensation of manganese-based composite cathode materials is mainly achieved by the transition metal cations gaining and losing electrons, accompanied by a small amount of anion redox. The ion valence change process of manganese-based composite cathode materials is described in detail as follows.

[0068] During the first week of charging, the iron ions in the manganese-based composite positive electrode material are converted from positive trivalent (Fe 3+ ) is oxidized to positive tetravalent (Fe 4+ ), while the manganese ion also changes from positive trivalent (Mn 3+ ) is oxidized to positive tetravalent (Mn 4+ ), oxygen ions are negative divalent (O 2- ) is oxidized to negative one (O - ); During the first cycle of discharge, the iron ion changes from positive tetravalent (Fe 4+ ) is reduced to trivalent (Fe 3+ ), similarly, manganese ions are also tetravalent (Mn 4+ ) is reduced to trivalent (Mn 3+ ), oxygen ions are negative monovalent (O - ) is reduced to negative divalent (O 2- ).

[0069] When the manganese-based composite positive electrode material provided by the present invention contains nickel element, during the first week of charging, the nickel ions will first be oxidized from positive divalent to positive trivalent, and then oxidized from positive trivalent to positive tetravalent; during the first week of discharging, the nickel ions will first be reduced from positive tetravalent to positive trivalent, and then reduced from positive trivalent to positive divalent.

[0070] During the charge and discharge cycle of sodium-ion batteries, except for the above-mentioned iron ions, manganese ions and nickel ions, other elements in the manganese-based composite positive electrode material do not change their valence during the battery cycle.

[0071] The ion valence change process of manganese-based composite positive electrode materials in the cycle after the first week of charge and discharge in sodium-ion batteries is consistent with the valence change process of the first week of charge and discharge.

[0072] In the process of element ion valence change of the high sodium content P2 phase manganese-based composite positive electrode material provided by the embodiment of the present invention during the first cycle of charge and discharge of the sodium ion battery, charge compensation is mainly achieved by the transition metal cations gaining and losing electrons, indicating that the battery capacity is not completely dependent on the anion redox reaction, but most of the capacity is obtained through cation redox.

[0073] The embodiment of the present invention provides a method for preparing the above-mentioned high sodium content P2 phase manganese-based composite positive electrode material, which is a sol-gel method and specifically includes the following steps.

[0074] Step 110, weighing sodium source material, manganese source material, iron source material, compound containing M element and compound containing N element as raw materials according to the stoichiometric ratio of the chemical formula of manganese-based composite positive electrode material, dissolving the raw materials in deionized water, stirring and mixing, adding chelating agent, and continuing to stir at a certain temperature to form a precursor gel.

[0075] Among them, the chemical formula of manganese-based composite positive electrode material is: Na x M y1 N y2 Fe y3 Mn z O 2 , wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9; M is an element doped to replace Mn in the transition metal position, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; N is an element doped to replace Mn in the transition metal position, including at least one of Ni, Mg and Cu.

[0076] The sodium source material includes one or more of sodium nitrate, sodium acetate, sodium carbonate, sodium bicarbonate, sodium oxalate and sodium hydroxide.

[0077] The manganese source material includes: manganese nitrate and / or manganese acetate.

[0078] The iron source material includes at least one of ferric nitrate, ferrous acetate, ferrous oxalate and ferrous lactate.

[0079] Compounds containing M elements include: 2+ , Li + , Nb 5+ , Ca 2+ , B 3+ 、Al 3+ 、Zr 4+ Sn 4+ 、Ti 4+ 、Ru 4+ , Sb 5+ Or Mo 6+ A compound containing at least one ion.

[0080] Compounds containing N include: 2+ Mg2+ , Cu 2+ A compound containing at least one ion.

[0081] The complexing agent is citric acid monohydrate; the mass ratio of the complexing agent to the raw material is 2:1.

[0082] The mass ratio of deionized water to raw materials is 20:1 to 30:1.

[0083] Step 120, placing the precursor gel in a muffle furnace and performing carbonization treatment under air atmosphere to obtain an intermediate product powder.

[0084] The carbonization treatment includes: heating the temperature to 300°C to 500°C at a heating rate of 2°C / min to 8°C / min, and keeping the temperature for 1 hour to 4 hours in an air atmosphere.

[0085] Step 130, pressing the intermediate product powder into discs, calcining them in an air atmosphere, and then naturally cooling them to room temperature to obtain a manganese-based composite positive electrode material with a high sodium content P2 phase.

[0086] The calcination treatment includes: heating the temperature to 800° C. to 1000° C. at a heating rate of 2° C. / min to 8° C. / min, and calcining for 10 to 20 hours in an air atmosphere.

[0087] In the present invention, when the calcination temperature in the above step 130 is in the range of 800°C to 1000°C, it can be any temperature value within this range, for example, it can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C, 1000°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The crystal structure of the manganese-based composite positive electrode material with a high sodium content P2 phase prepared within this calcination temperature range is a P2 phase, and has good specific capacity and cycle stability.

[0088] The preparation method provided in the embodiment of the present invention is applicable to the above-mentioned chemical formula Na x M y1 N y2 Fe y3 Mn z O 2 All high-sodium-content P2 phase manganese-based composite positive electrode materials contained in it are universal.

[0089] The above-mentioned high sodium content P2 phase manganese-based composite positive electrode material provided in the embodiment of the present invention can be used as a positive electrode active material to prepare a positive electrode sheet. The preparation of the positive electrode sheet adopts a conventional preparation method, which can specifically include the following steps.

[0090] Step 210: Grind and mix the manganese-based composite positive electrode material with a high sodium content P2 phase and a conductive additive, mix them evenly, and obtain a mixed powder.

[0091] The conductive additives include: one or more of conductive carbon black super p, acetylene black, carbon nanotubes, Ketjen black, and conductive graphite, preferably conductive carbon black super p; the mass ratio of the conductive additives to the manganese-based composite positive electrode material is 0 to 30 wt%.

[0092] The grinding and mixing method adopts the conventional method known in the art, and the manganese-based composite positive electrode material and the conductive additive can be mixed evenly.

[0093] Step 220, adding a binder to the mixed powder, adding a solvent, and continuing to grind evenly to obtain a mixed slurry.

[0094] The binder includes one or more of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE), and polyimide (PI), preferably PVDF; the mass ratio of the binder to the manganese-based composite positive electrode material is 0 to 30 wt%.

[0095] The solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate, ethylene carbonate or diethylene carbonate, and N-methylpyrrolidone is preferred.

[0096] Step 230, coating the mixed slurry on the current collector, drying it in an oven, and cutting it to obtain the positive electrode sheet.

[0097] The current collector includes but is not limited to aluminum foil; the drying conditions are: vacuum baking at 90°C to 120°C for 5 to 10 hours, and the cutting size is 8×8mm 2 The cut electrodes are cut into small squares or 12 mm diameter discs, and then quickly transferred to an argon-filled glove box for subsequent use.

[0098] An embodiment of the present invention also provides a sodium ion battery, which includes the above-mentioned manganese-based composite positive electrode material positive electrode plate containing a high sodium content P2 phase, as well as a diaphragm, an electrolyte or a solid electrolyte, and a negative electrode plate; the operating voltage range of the sodium ion battery is between 2V and 4.3V.

[0099] An embodiment of the present invention provides a use of the above-mentioned sodium ion battery, which can be used in large-scale energy storage equipment for solar energy and wind power generation, or energy storage equipment for smart grid peak regulation, distributed power stations, backup power supplies, communication base stations, and electric vehicles.

[0100] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the manganese-based composite positive electrode material of the high sodium content P2 phase of the present invention are respectively described below with multiple specific examples.

[0101] Example 1 This embodiment provides a process for preparing a manganese-based composite positive electrode material with a high sodium content P2 phase. The chemical formula of the manganese-based composite positive electrode material is Na 0.8 Li 0.1 Fe 0.1 Mn 0.8 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.1, y2=0, y3=0.1, z=0.8, M is Li element), the specific preparation process is as follows.

[0102] (1) Weigh the sodium source material anhydrous sodium acetate (CH 3 COONa), manganese source material manganese acetate tetrahydrate ((CH 3 COO 2 Mn·4H 2 O), iron source material iron nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), Li-ion-containing compounds lithium acetate dihydrate (CH 3 COOLi·2H 2 O) as a raw material, the raw material was dissolved in 20g of deionized water, stirred and mixed for 30min, and then 2g of citric acid monohydrate, a complexing agent, was added, and stirring was continued at 80°C for 10 hours to form a precursor gel.

[0103] (2) The precursor gel is placed in a muffle furnace and heated to 400°C at a heating rate of 5°C / min in an air atmosphere. After sintering for 2 hours, the raw material is carbonized to obtain an intermediate product powder.

[0104] (3) The intermediate product powder is pressed into a compact disc and placed in a muffle furnace. The temperature is raised to 850°C at a heating rate of 5°C / min in an air atmosphere for calcination for 15 hours. After the calcination is completed, the temperature is naturally cooled to room temperature to obtain a manganese-based composite positive electrode material with a high sodium content P2 phase, with a chemical formula of Na 0.8 Li 0.1 Fe 0.1 Mn 0.8 O 2 .

[0105] The high sodium content P2 phase manganese-based composite positive electrode material Na prepared in this embodiment 0.8 Li 0.1 Fe0.1 Mn 0.8 O 2 The XRD pattern of Figure 3 As shown, it can be seen that the crystal structure of the manganese-based composite positive electrode material prepared in this embodiment is P2 phase.

[0106] The manganese-based composite positive electrode material with a high sodium content P2 phase prepared in this embodiment is used to prepare a positive electrode plate, and a sodium ion battery is assembled using the positive electrode plate for testing. The specific assembly and testing process is as follows.

[0107] (1) The manganese-based composite positive electrode material powder of the high sodium content P2 phase is ground and mixed with carbon black to obtain a mixed powder, and then a binder PVDF is added, wherein the mass ratio of the manganese-based composite positive electrode material powder, carbon black and binder is 70:20:10, and the total weight is 0.1 g.

[0108] (2) Add an appropriate amount of N-methylpyrrolidone (NMP) solution and continue grinding in a dry environment at room temperature to form a mixed slurry.

[0109] (3) The mixed slurry was evenly coated on the current collector aluminum foil, dried at 120 °C for 10 hours under vacuum conditions, and cut into 8 × 8 mm 2 The small square electrode was then quickly transferred to an argon-filled glove box for subsequent use.

[0110] (4) The positive electrode obtained in the above steps is assembled with the diaphragm, electrolyte, and negative electrode in a glove box filled with argon to form a sodium ion battery. Metallic sodium is used as the counter electrode, and the sodium ion battery electrolyte uses NaClO with a molar mass of 1 mol / L. 4 The solution (in which the solvent is 100 Vol% polycarbonate PC and 5 Vol% fluoroethylene carbonate FEC) uses a glass fiber membrane as a battery separator and is assembled into a sodium ion battery (CR2032 button cell) according to conventional processes.

[0111] The assembled sodium-ion battery was tested using a constant current charge and discharge mode with a current density of 1C, a discharge cut-off voltage of 2V, and a charge cut-off voltage of 4.3V.

[0112] The charge and discharge curve of the sodium ion battery assembled in this embodiment at 1C rate in the first week is as follows: Figure 5 As shown, the cycle capacity curve is as follows Figure 7 As shown, at 1C, the first week discharge capacity is 85.9 mAh / g, and the 100-week capacity retention rate is 99.8%. The test data is summarized in Table 1.

[0113] Example 2 This embodiment provides a preparation process and performance test of a manganese-based composite positive electrode material with a high sodium content P2 phase. The chemical formula of the prepared positive electrode material is Na 0.8 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.1, y2=0.1, y3=0.1, z=0.7, M is Li element, and N is Ni element).

[0114] The preparation process of the high sodium content P2 phase manganese-based composite positive electrode material provided in this embodiment is different from that in embodiment 1 in that the nickel source material nickel acetate tetrahydrate ((CH 3 COO 2 Ni·4H 2 O) as raw material, and anhydrous sodium acetate (CH 3 COONa), manganese source material manganese acetate tetrahydrate ((CH 3 COO 2 Mn·4H 2 O), iron source material iron nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), Li-ion-containing compounds lithium acetate dihydrate (CH 3 COOLi·2H 2 O) as raw materials, dissolved in 20g of deionized water and stirred. The other preparation process is exactly the same as that of Example 1.

[0115] The XRD pattern of the high sodium content P2 phase manganese-based composite positive electrode material prepared in Example 2 is as follows: Figure 3 , it can be judged from the XRD diagram that the crystal structure of the material prepared in Example 2 is P2 phase.

[0116] The manganese-based composite positive electrode material with high sodium content P2 phase prepared in this embodiment is used to prepare a positive electrode plate, and the positive electrode plate is used to assemble a sodium ion battery for testing. The positive electrode plate preparation process, battery assembly process and testing process are the same as those in Example 1.

[0117] The charge and discharge curve of the sodium ion battery assembled in Example 2 at 1C rate in the first week is as follows: Figure 5 As shown, the charge and discharge curves from the first week to the fifth week at 1C are as follows Figure 6 As shown, the cycle capacity curve is as follows Figure 7 As shown, at 1C, the first week discharge capacity is 96.7 mAh / g, and the 100-week capacity retention rate is 91.2%. The test data is summarized in Table 1.

[0118] The preparation method of the high sodium content P2 phase manganese-based composite positive electrode material, CR2032 button battery assembly and testing method provided in Examples 3 to 10 are the same as those in Example 2, the specific difference being the different contents of Li element, Fe element, Ni element and Mn element, which are as follows.

[0119] Example 3 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.05 Ni 0.1 Fe 0.1 Mn 0.75 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.05, y2=0.1, y3=0.1, z=0.75, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 3 in the figure, it can be seen that the crystal structure is P2 phase; the cycle capacity curve of the test battery is as follows Fig. 9 As shown, at 1C, the first week discharge capacity is 90.1mAh / g, the 100-week capacity retention rate is 81.6%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0120] Example 4 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.1 Ni 0.05 Fe 0.1 Mn 0.75 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.1, y2=0.05, y3=0.1, z=0.75, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 4 in the figure, it can be seen that the crystal structure is P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 100.2mAh / g, the 100-week capacity retention rate is 99.6%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0121] Example 5 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.07 Ni 0.11 Fe 0.12 Mn 0.7 O 2(wherein, corresponding to the general formula x=0.8, y1=0.07, y2=0.11, y3=0.12, z=0.7, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 5, it can be seen that the crystal structure is a P2 phase.

[0122] The charge and discharge curve of the sodium ion battery assembled in this embodiment at 1C rate in the first week is as follows: Figure 5 As shown, the cycle capacity curve of the test battery is as follows Figure 7 As shown, the charge and discharge curves for the first five weeks at 1C are as follows Figure 8 As shown in the figure, the first week discharge capacity is 99.9mAh / g at 1C, the 100-week capacity retention rate is 97.4%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1. Fig.10 As shown, at rates of 0.5C, 1C, 2C, 3C and 5C, the discharge capacities of Example 5 are 109.8 mAh / g, 103.8 mAh / g, 97.5 mAh / g, 93.9 mAh / g and 89.9 mAh / g, respectively, and the specific capacity at 5C rate can reach 82.2% of that at 0.5C rate, with excellent rate performance.

[0123] Example 6 The chemical formula of the prepared high sodium content P2 phase manganese-based composite cathode material is Na 0.8 Li 0.04 Ni 0.15 Fe 0.13 Mn 0.68 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.04, y2=0.15, y3=0.13, z=0.68, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 6 in the figure, it can be seen that the crystal structure is a P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 97.7mAh / g, the 100-week capacity retention rate is 96.2%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0124] Example 7 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.09 Ni 0.06 Fe 0.15 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.09, y2=0.06, y3=0.15, z=0.7, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 7 in the figure, it can be seen that the crystal structure is a P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 93.5mAh / g, the 100-week capacity retention rate is 88.1%, the operating voltage range is 2V to 4.3V, and the test data is summarized in Table 1.

[0125] Example 8 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.06 Ni 0.08 Fe 0.16 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.06, y2=0.08, y3=0.16, z=0.7, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 8 in the figure, it can be seen that the crystal structure is a P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 93.8mAh / g, the 100-week capacity retention rate is 88.2%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0126] Example 9 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.08 Ni 0.04 Fe 0.17 Mn 0.71 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.08, y2=0.04, y3=0.17, z=0.71, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 9 in the figure, it can be seen that the crystal structure is P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 90.9mAh / g, the 100-week capacity retention rate is 87.1%, the operating voltage range is 2V to 4.3V, and the test data is summarized in Table 1.

[0127] Example 10 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Li 0.06 Ni 0.05 Fe 0.18 Mn 0.71 O 2(wherein, corresponding to the general formula x=0.8, y1=0.06, y2=0.05, y3=0.18, z=0.71, M is Li element, N is Ni element), its XRD is as follows Figure 3 As shown in Example 10 in the embodiment, it can be seen that the crystal structure is P2 phase; the cycle capacity curve of the test battery is as shown in Fig. 9 As shown, at 1C, the first week discharge capacity is 95.2mAh / g, the 100-week capacity retention rate is 89.2%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0128] Embodiment 11 This embodiment provides a preparation process and performance test of a manganese-based composite positive electrode material with a high sodium content P2 phase. The chemical formula of the prepared positive electrode material is Na 0.8 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.05, y2=0.15, y3=0.1, z=0.7, M is Mg element, and N is Cu element). The specific preparation and testing process is as follows.

[0129] (1) Weigh the sodium source material anhydrous sodium acetate (CH 3 COONa), manganese source material manganese acetate tetrahydrate ((CH 3 COO 2 Mn·4H 2 O), iron source material iron nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), copper source material anhydrous copper acetate ((CH 3 COO 2 Cu) and magnesium source material magnesium acetate tetrahydrate ((CH 3 COO 2 Mg·4H 2 O) as a raw material, the raw material was dissolved in 20g of deionized water, stirred and mixed for 30min, and then 2g of citric acid monohydrate, a complexing agent, was added, and then stirred at 80°C for 10 hours to form a precursor gel.

[0130] (2) The precursor gel is placed in a muffle furnace and heated to 400°C at a heating rate of 5°C / min in an air atmosphere. After sintering for 2 hours, the raw material is carbonized to obtain an intermediate product powder.

[0131] (3) The intermediate product powder is pressed into a compact disc and placed in a muffle furnace. The temperature is raised to 850°C at a heating rate of 5°C / min in an air atmosphere for calcination. The sintering time is 15 hours. After the calcination is completed, the temperature is naturally cooled to room temperature to obtain the manganese-based composite positive electrode material with a high sodium content P2 phase, the chemical formula of which is Na 0.8 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 .

[0132] The high sodium content P2 phase manganese-based composite positive electrode material Na prepared in this embodiment 0.8 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 The XRD pattern of Figure 4 As shown, it can be seen that the crystal structure is P2 phase.

[0133] The manganese-based composite positive electrode material Na with high sodium content P2 phase prepared in this embodiment 0.8 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 A positive electrode sheet was prepared, and a sodium ion battery was assembled using the positive electrode sheet for testing. The specific testing process is as follows.

[0134] (1) The high sodium content P2 phase manganese-based composite positive electrode material powder is mixed with carbon black and a binder PVDF in a mass ratio of 70:20:10.

[0135] (2) Add an appropriate amount of NMP solution and grind in a dry environment at room temperature to form a slurry.

[0136] (3) The slurry was evenly coated on the current collector aluminum foil, dried at 120 °C for 10 hours under vacuum conditions, and cut into 8 × 8 mm 2 The square electrode was then quickly transferred to an argon-filled glove box for subsequent use.

[0137] (4) The positive electrode obtained in the above steps is assembled with the diaphragm, electrolyte, and negative electrode in a glove box filled with argon to form a sodium ion battery. Metallic sodium is used as the counter electrode, and the sodium ion battery electrolyte uses NaClO with a molar mass of 1 mol / L. 4 The solution (in which the solvent is 100 Vol% polycarbonate PC and 5 Vol% fluoroethylene carbonate FEC) uses a glass fiber membrane as a battery separator and is assembled into a sodium ion battery (CR2032 button cell) according to conventional processes.

[0138] The assembled sodium-ion battery was tested using a constant current charge and discharge mode with a current density of 1C, a discharge cut-off voltage of 2V, and a charge cut-off voltage of 4.3V.

[0139] The charge and discharge curve of the sodium ion battery assembled in this embodiment at 1C rate in the first week is as follows: Fig.11 As shown, the charge and discharge curves for the first five weeks are as follows Fig.12 As shown, the cycle capacity curve is as follows Fig.13 As shown, at 1C, the first week discharge capacity is 82.7 mAh / g, and the 100-week capacity retention rate is 83.1%. The test data is summarized in Table 2.

[0140] The preparation method of the high sodium content P2 phase manganese-based composite positive electrode material, CR2032 button battery assembly and testing method provided in Examples 12 to 14 are the same as those in Example 10, with the specific difference being the different doped M elements, which are as follows.

[0141] Example 12 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Ni 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.15, y2=0.05, y3=0.1, z=0.7, M is Cu element, N is Ni element), its XRD is as follows Figure 4 As shown in Example 12, it can be seen that the crystal structure is P2 phase; the first week charge and discharge curve of the sodium ion battery assembled in this embodiment at 1 C is as shown in Fig.11 As shown, the cycle capacity curve is as follows Fig.13 As shown, at 1C, the first week specific capacity is 94.9 mAh / g, the 100-week capacity retention rate is 80.2%, the operating voltage range is 2V to 4.3V, and the test data is summarized in Table 2.

[0142] Embodiment 13 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Zn 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.05, y2=0.15, y3=0.1, z=0.7, M is Zn element, N is Cu element), its XRD is as follows Figure 4As shown in Example 14, it can be seen that the crystal structure is P2 phase; the first week charge and discharge curve of the sodium ion battery assembled in this embodiment at 1C is as shown in Fig.11 As shown, the cycle capacity curve is as follows Fig.13 As shown, at 1C, the first week specific capacity is 94.8mAh / g, the 100-week capacity retention rate is 76.9%, the operating voltage range is 2V to 4.3V, and the test data is summarized in Table 2.

[0143] Embodiment 14 The chemical formula of the high sodium content P2 phase manganese-based composite positive electrode material prepared in this embodiment is Na 0.8 Al 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 (wherein, corresponding to the general formula x=0.8, y1=0.05, y2=0.15, y3=0.1, z=0.7, M is Al element, N is Cu element), its XRD is as follows Figure 4 As shown in Example 15, it can be seen that the crystal structure is P2 phase; the first week charge and discharge curve of the sodium ion battery assembled in this embodiment at 1C is as shown in Fig.11 As shown, the cycle capacity curve is as follows Fig.13 As shown, at 1C, the first week specific capacity is 90.8mAh / g, the 100-week capacity retention rate is 73.1%, the operating voltage range is 2V to 4.3V, and the test data is summarized in Table 2.

[0144] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments.

[0145] Comparative Example 1 Low sodium content 0.67 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 For comparative example 1, the preparation method is basically the same as that of Example 2, the only difference is the quality of the sodium source material, and the subsequent preparation materials and testing process are the same as those of Example 2. 0.67 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 The crystal structure of the P2 phase. The first week charge and discharge curve of the test under 1C is as follows Fig.15 As shown, the charge and discharge curves for the first five weeks are as follows Fig.14 As shown, the cycle capacity curve is as follows Fig.16As shown, at 1C, the first week specific capacity is only 84.7mAh / g, the 100-week capacity retention rate is 89.6%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 1.

[0146] Comparative Example 2 Low sodium content 0.67 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 This is comparative example 2. The preparation method is basically the same as that of Example 11, except for the quality of the sodium source material. The subsequent preparation materials and testing process are the same as those of Example 11. 0.67 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 The crystal structure of the P2 phase. The first week charge and discharge curve of the 1C test is as follows: Fig.18 As shown, the charge and discharge curves for the first five weeks are as follows Fig.17 As shown, the cycle capacity curve is as follows Fig.19 As shown, at 1 C, the first week specific capacity is only 75.4 mAh / g, the 100-week capacity retention rate is 86.2%, and the operating voltage range is 2V to 4.3V. The test data is summarized in Table 2.

[0147] Table 1 is a summary of the chemical formulas of the materials prepared in Examples 1-10 and Comparative Example 1 and the test data of the assembled batteries, as follows.

[0148] Table 2 is a summary of the chemical formulas of the materials prepared in Examples 11-14 and Comparative Example 2 and the test data of the assembled batteries, as follows.

[0149] Through the test data in Table 1 and Table 2, as well as the attached Figure 3-19 To illustrate the performance of the manganese-based composite positive electrode material of the high sodium content P2 phase of the present invention.

[0150] pass Figure 3 , Figure 4 From the XRD of the material, it can be seen that the obtained high sodium content P2 phase manganese-based composite positive electrode materials are all pure phase structures, proving that M ions and N ions have successfully replaced manganese and doped into the structure.

[0151] pass Figure 5 and Figure 7It can be seen that Example 2 is doped with Ni element compared to Example 1, and Example 5 changes the doping ratio of each element in the material compared to Example 2, which has different degrees of electrochemical effects on the material. Among them, the first week specific capacity of Example 1 is 85.9 mAh / g, and the first week specific capacity of Example 2 is 96.7 mAh / g, which proves that the introduction of a small amount of Ni element has a positive effect on the improvement of the material specific capacity. The 100-week capacity retention rate of Example 2 is 91.2%, and the 100-week capacity retention rate of Example 5 is 97.4%, which proves that changing the ratio of element doping in the positive electrode material can affect the cycle stability of the positive electrode material.

[0152] pass Fig. 9 It can be seen that the 100-week capacity retention rates of Examples 3-10 are 81.6%, 99.6%, 97.4%, 96.2%, 88.1%, 88.2%, 87.1% and 89.2%, respectively, proving that the ratio of element doping has a great influence on the cycle stability of the positive electrode material, and the study found that the Na prepared in Example 5 0.8 Li 0.07 Ni 0.11 Fe 0.12 Mn 0.7 O 2 The performance is the best. The specific capacity reaches 123mAh / g at a rate of 0.1C, and the capacity retention rate is 97.4% after 100 cycles at a rate of 1C.

[0153] pass Fig.15 and Fig.16 It can be seen that when the element composition and content of the transition metal layer remain unchanged, the low sodium content P2 phase layered oxide Na prepared in Comparative Example 1 0.67 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 The specific capacity in the first week was only 84.7 mAh / g, and the capacity retention rate after 100 weeks was also lower than that of the Na prepared in Example 2. 0.8 Li 0.1 Ni 0.1 Fe 0.1 Mn 0.7 O 2 , proving that increasing the sodium content plays a great positive role in improving the specific capacity and cycle stability of the material.

[0154] pass Fig.10 It can be seen that the preferred material Na 0.8 Li 0.07 Ni 0.11 Fe 0.12 Mn 0.7 O 2(Prepared in Example 5) At rates of 0.5C, 1C, 2C, 3C and 5C, the discharge capacities of Example 5 are 109.8mAh / g, 103.8mAh / g, 97.5mAh / g, 93.9mAh / g and 89.9mAh / g, respectively, and the specific capacity at 5C rate can reach 82.2% of that at 0.5C rate, with excellent rate performance.

[0155] Examples 11-14 of the present invention were synthesized using materials with different Fe and Mn contents, different M elements, and different N elements. Figure 4 The XRD images of Examples 11-14 show that the crystal structures are all P2 phases. Figure 11-13 The electrochemical performance of Examples 11 to 14 proves that different M and N elements have a great influence on the specific capacity and cycle stability of the material, and the preferred M element is Li and the preferred N element is Ni. Fig.18 and Fig.19 It can be seen that when the element composition and content of the transition metal layer remain unchanged, the low sodium content P2 phase layered oxide Na prepared in Comparative Example 2 0.67 Mg 0.05 Cu 0.15 Fe 0.1 Mn 0.7 O 2 The specific capacity in the first week was only 75.4 mAh / g, which further proves that increasing the sodium content plays a great positive role in improving the specific capacity and cycle stability of the positive electrode material.

[0156] The inventors found in the process of synthesizing materials that the synthesis of materials with different crystalline phase structures needs to be obtained by changing the sodium content in the materials. According to the chemical formula of the manganese-based composite positive electrode material of the present invention (Na x M y1 N y2 Fe y3 Mn z O 2 , wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9), only changing the content range of sodium in the general formula, while keeping the contents of other elements unchanged, it is also difficult to synthesize pure O3 and P3 phases, but still retain the main structure of the P2 phase, unless the proportion of the transition metal layer is changed, that is, to further illustrate that by the preparation method of the present invention, and by weighing the raw materials according to the molar ratio of each element in the chemical formula of the present invention, the manganese-based composite positive electrode material obtained has a pure P2 phase crystal structure.

[0157] An embodiment of the present invention provides a method for preparing a manganese-based composite positive electrode material with a high sodium content P2 phase, wherein the raw materials are subjected to a sol-gel method to form a precursor gel, and then subjected to a carbonization and calcination process to obtain a manganese-based composite positive electrode material with a high sodium content P2 phase; the preparation method is simple to operate, the raw materials are cheap and easily available, the cost is low, and it can be suitable for large-scale production.

[0158] The high sodium content P2 phase manganese-based composite positive electrode material obtained by the preparation method provided in the embodiment of the present invention, firstly, the higher sodium content can effectively improve the first-week coulomb efficiency, first-week charging capacity and cycle stability of the material and can inhibit the material from the P2 phase to the O2 phase transformation under the high voltage range; secondly, the low-cost Fe element is introduced into the material to replace the Ni element, and the Fe element and the Mn element work synergistically to reduce the content of the Ni element to an extremely low level or completely exclude the Ni element, which not only reduces the material cost, but also improves the safety of the material, which is conducive to industrial production. At the same time, by adjusting the proportion of each element in the material, the problems of large polarization and poor cycle stability that may be caused by the Fe element are avoided.

[0159] The sodium ion battery prepared by using the manganese-based composite positive electrode material with a high sodium content P2 phase provided by the embodiment of the present invention has the characteristics of high specific capacity, excellent cycle performance, good safety performance and high practical value; the sodium ion battery containing the manganese-based composite positive electrode material with a high sodium content P2 phase is widely used and can be applied to large-scale energy storage equipment such as solar power generation, wind power generation, electric vehicles, smart grid peak regulation, distributed power stations, backup power supplies or communication base stations.

[0160] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A manganese-based composite positive electrode material with a high sodium content P2 phase, characterized in that: The chemical formula of the manganese-based composite positive electrode material is: Na x M y1 N y2 Fe y3 Mn z O2, wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9; M is an element doped to replace the transition metal position Mn, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; N is an element doped to replace the transition metal position Mn, including at least one of Ni, Mg and Cu; The operating voltage of the manganese-based composite positive electrode material when used in a sodium ion battery is between 2V and 4.3V.

2. The manganese-based composite positive electrode material according to claim 1, characterized in that: The manganese-based composite positive electrode material is used in a sodium ion battery. During the first week of charging, the iron ions are oxidized from positive trivalent to positive tetravalent, while the manganese ions are oxidized from positive trivalent to positive tetravalent, and the oxygen ions are oxidized from negative divalent to negative monovalent; during the first week of discharging, the iron ions are reduced from positive tetravalent to positive trivalent, while the manganese ions are reduced from positive tetravalent to positive trivalent, and the oxygen ions are reduced from negative monovalent to negative divalent; When the manganese-based composite positive electrode material contains nickel elements, during the first cycle of charging, the nickel ions will first be oxidized from positive divalent to positive trivalent, and then from positive trivalent to positive tetravalent; during the first cycle of discharging, the nickel ions will first be reduced from positive tetravalent to positive trivalent, and then from positive trivalent to positive divalent; Other elements in the manganese-based composite positive electrode material do not undergo valence changes; The valence change process of the manganese-based composite positive electrode material after the first cycle of charge and discharge is consistent with the valence change process of the first cycle of charge and discharge.

3. The manganese-based composite positive electrode material according to claim 1, characterized in that: The space group of the manganese-based composite positive electrode material is any one of P63 / mmc, P6322 or P63 / mcm, and the crystal structure is P2 phase.

4. A method for preparing a manganese-based composite positive electrode material with a high sodium content P2 phase as described in any one of claims 1 to 3, characterized in that: The preparation method is a sol-gel method, comprising: According to the stoichiometric ratio of the chemical formula of the manganese-based composite positive electrode material, a sodium source material, a manganese source material, an iron source material, a compound containing an M element, and a compound containing an N element are weighed as raw materials, the raw materials are dissolved in deionized water, a complexing agent is added after stirring and mixing, and stirring is continued at a certain temperature to form a precursor gel; Placing the precursor gel in a muffle furnace and performing carbonization treatment under air atmosphere to obtain an intermediate product powder; The intermediate product powder is pressed into a disc, calcined in an air atmosphere, and then naturally cooled to room temperature to obtain the manganese-based composite positive electrode material with a high sodium content P2 phase; The chemical formula of the manganese-based composite positive electrode material is: Na x M y1 N y2 Fe y3 Mn z O2, wherein x, y1, y2, y3, z are the molar percentages of the corresponding elements respectively, and the relationship between y1, y2, y3 and z satisfies y1+y2+y3+z=1, 0.75≤x≤0.9, 0<y1≤0.2, 0<y2≤0.2, 0.05≤y3≤0.2, 0.6≤z≤0.9; M is an element doped to replace Mn in the transition metal position, including at least one of Zn, Li, Nb, Ca, B, Al, Zr, Sn, Ti, Ru, Nb, Sb or Mo; N is an element doped to replace Mn in the transition metal position, including at least one of Ni, Mg and Cu.

5. The preparation method according to claim 4, characterized in that: The sodium source material includes: one or more of sodium nitrate, sodium acetate, sodium carbonate, sodium bicarbonate, sodium oxalate, and sodium hydroxide; The manganese source material includes: manganese nitrate and / or manganese acetate; The iron source material comprises: at least one of ferrous nitrate, ferrous acetate, ferrous oxalate, and ferrous lactate; The compounds containing M elements include: 2+ , Li + , Nb 5+ , Ca 2+ , B 3+ 、Al 3+ 、Zr 4+ Sn 4+ 、Ti 4+ 、Ru 4+ , Sb 5+ Or Mo 6+ A compound containing at least one ion; The compounds containing N element include: 2+ Mg 2+ , Cu 2+ A compound containing at least one ion; The complexing agent is citric acid monohydrate; the mass ratio of the complexing agent to the raw material is 2:1; The mass ratio of the deionized water to the raw material is 20:1 to 30:

1.

6. The preparation method according to claim 4, characterized in that: The carbonization treatment comprises: heating the temperature to 300° C. to 500° C. at a heating rate of 2° C. / min to 8° C. / min, and keeping the temperature for 1 hour to 4 hours in an air atmosphere.

7. The preparation method according to claim 4, characterized in that: The calcination treatment comprises: heating to 800° C. to 1000° C. at a heating rate of 2° C. / min to 8° C. / min, and calcining for 10 to 20 hours in an air atmosphere.

8. A positive electrode sheet, characterized in that: The positive electrode plate comprises the manganese-based composite positive electrode material of the P2 phase with a high sodium content as described in any one of claims 1 to 3.

9. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet as claimed in claim 8; the sodium ion battery further comprises a separator, an electrolyte or a solid electrolyte, and a negative electrode sheet; The operating voltage range of the sodium ion battery is between 2V and 4.3V.

10. A use of the sodium ion battery according to claim 9, characterized in that: The sodium ion battery is used in one or more of solar energy, wind energy generation, smart grid peak regulation, distributed power stations, backup power supplies, communication base stations, and energy storage devices for electric vehicles.

Citation Information

Patent Citations

  • Sodium-magnesium-iron-manganese-based layered oxide material as well as preparation method and application thereof

    CN113078298A

  • Five-membered layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN114927663A

  • Multi-metal co-regulated layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115939369A

  • Nickel-manganese-based layered oxide positive electrode material for sodium ion battery and preparation method of nickel-manganese-based layered oxide positive electrode material

    CN117117197A

  • Multi-element doped iron-manganese series sodium ion battery positive electrode material, preparation method and battery

    CN118630198A